Perspektif Hukum Islam terhadap mekanisme Autodebet bagi Kepatuhan Peserta Asuransi BPJS - Muhajirin, Muhajirin; Pratama, Herdifa; Tutrisno, Irwan; Jannati, Nurlaili; Ferly, Bobby (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This study examines the autodebit system for BPJS Kesehatan contributions among Non-Wage Recipient Workers from an Islamic legal perspective. Using a qualitative juridical-normative approach through library research, this study combines Islamic jurisprudence, regulatory frameworks, and previous studies. The findings indicate that autodebit effectively enhances payment discipline, reduces arrears, and sustains participation. From an Islamic perspective, autodebit is permissible as long as the contract is clear, voluntary, and free from gharar, riba, and coercion. It also aligns with the maqāṣid al-sharī‘ah principles of justice, facilitation, and public welfare. This study provides reassurance for Muslim participants that the autodebit mechanism is consistent with Islamic values and supports the sustainability of the JKN program in Indonesia.